Effect of Herb Treatments on the Storability of Sweet Oranges (Citrus sinensis Osberk) Stored in Evaporative Cooler - Adekalu, O A; Agboola , D A (Journal of Postharvest Technology, 2015)
Large quantities of oranges produced in Nigeria are wasted during storage.  Sweet oranges due to their perishable nature deteriorate fast. Causes of spoilage  are rather physiological or pathological factors. There is need for research  breakthrough to minimize or reduce the post harvest losses encountered by  orange farmers in Nigeria. Thymus vulgaris (Thyme), Allium sativum (Garlic),  Cympobogon citratus (lemon grass) and Eugenia aromatica (Clove) aqueous  extracts were prepared and used to treat oranges before storage in evaporative  coolers. Harvested matured green oranges were dipped inside 5, 10, and 15%  aqueous extracts each and air dried. The treated sweet oranges were stored  inside Tin in Pot cooler A and Pot in Pot cooler B evaporative coolers.  Percentage of ripening of sweet oranges was 40% and 45% for each cooler,  while control was 100% at the end of the week. The treated oranges stored for  between 35 to 52 days. Sensory evaluation, marketability, and acceptability were  rated good at the end at the end of the study.
Keywords: Sweet orange; Thyme Garlic; Lemon grass extract; Evaporative cooling